2005
DOI: 10.1063/1.1888505
|View full text |Cite
|
Sign up to set email alerts
|

Role of local structure on motions on the potential energy landscape for a model supercooled polymer

Abstract: We have conducted detailed Monte Carlo and molecular dynamics simulations of a model glass forming polymeric system near its apparent glass transition temperature. We have characterized the local structure of the glass using a Voronoi-Delaunay analysis of local particle arrangements. After a perturbative face elimination, we find that a significant fraction of Voronoi polyhedra consist of 12 pentagonal faces, a sign of icosahedral ordering. Further, we have identified metabasins of particle vibrations on the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…Insights have also been realized using local measures of symmetry to elucidate local mobility, e.g. icosohedral order [11,14]; or the recent work of Shintani and Tanaka in which less mobile regions were shown to correlate well to structured, crystal-like domains [15]. Recently, the local Debye-Waller factor has been shown to correlate to the dynamic propensity [16], firmly establishing the connection between local dynamics at short and long times.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Insights have also been realized using local measures of symmetry to elucidate local mobility, e.g. icosohedral order [11,14]; or the recent work of Shintani and Tanaka in which less mobile regions were shown to correlate well to structured, crystal-like domains [15]. Recently, the local Debye-Waller factor has been shown to correlate to the dynamic propensity [16], firmly establishing the connection between local dynamics at short and long times.…”
mentioning
confidence: 99%
“…More recently, several studies have sought a correlation at the microscopic level, e.g. between local free volume and local mobility, with more success in some systems [10,11] than in others [12]. A notable absence of correlation between the local volume and the local Debye-Waller factor has been reported recently [13].…”
mentioning
confidence: 99%
“…It was concluded that the proper inclusion of many-body static correlations in theories of the glass transition appears crucial for the description of the dynamics of fragile glass formers [56]. The search of a link between structural ordering and slow dynamics motivated several studies in liquids [57][58][59][60][61], colloids [62][63][64] and polymeric systems [62,[65][66][67][68][69][70]. We also note that the elastic models of the glass transition conclude that the relaxation is related to the elastic shear modulus, a quantity which is set by the arrangement of the particles in mechanical equilibrium and their mutual interactions [9,39].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding how these these types of structural features connect to relaxation processes of supercooled liquids is an active area of research (see, e.g., Refs. 27,28,29,30).…”
Section: Introductionmentioning
confidence: 99%